1997
DOI: 10.1177/002199839703100404
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of Hole Machining Defects in Pin-Loaded Composite Laminates

Abstract: The propagation of hole machining defects in pin-loaded carbon/epoxy laminates subjected to uniaxial tension fatigue loading was investigated using two non-destructive examination (NDE) techniques. The KTH-method, a new method which gives defect-free1 holes, was used to machine holes in specimens. For comparison, holes were also machined using two traditional methods (DIXI and Dagger drills) causing varying extent of damage. X-ray radiography and computerised tomography were used to give two- and three-dimensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2007
2007
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…The influence of defects generated after hole making on the strength and fatigue life of composite laminates subjected to static and fatigue loading were studied by Tagliaferri et al [26], Persson et al [27], Ramkumar et al [28] and Xu et al [29]. In general, the results indicated that tool material and geometry slightly affect the fatigue life of composites.…”
Section: Quality Of the Machined Holesmentioning
confidence: 99%
“…The influence of defects generated after hole making on the strength and fatigue life of composite laminates subjected to static and fatigue loading were studied by Tagliaferri et al [26], Persson et al [27], Ramkumar et al [28] and Xu et al [29]. In general, the results indicated that tool material and geometry slightly affect the fatigue life of composites.…”
Section: Quality Of the Machined Holesmentioning
confidence: 99%
“…Delamination and surface finish in drilling composite materials have been found to be influenced by a number of factors such as feed rate, cutting speed, drill geometry, tool wear and tool material. Delamination remains the most serious damage mode as it reduces severely the load carrying capacity of laminated composite structures and, therefore, must be avoided (Abrate [8], Persson et al [9,10]). The importance of tool geometry in delamination reduction is evidenced by several authors.…”
Section: Introductionmentioning
confidence: 99%
“…The properties of laminate around the hole can be weakened/deteriorated compared to their nominal values. This deterioration can be a result of the drilling technology, and on the other hand, the cyclic load during the service of the structure [32][33][34]. Analysis of the hole machining effects can be found in refs.…”
Section: Introductionmentioning
confidence: 99%